A new red-eyed treefrog of Agalychnis (Anura: Hylidae: Phyllomedusinae) from middle Magdalena River valley of Colombia with comments on its phylogenetic position - Rivera-Correa, Mauricio; Duarte-Cubides, Felipe; Rueda-Almonacid, José Vicente; Daza, Juan M. (Zootaxa, 2013)
We describe a new species of the charismatic red-eyed treefrogs (genus Agalychnis) from middle Magdalena River valley of Colombia (05°50’8.04’’N, 74°50’16.55’’W, 380 m a.s.l.). The new species is readily distinguished from all species members of the group by having orange flanks with small white warts. Phylogenetic analysis of DNA sequences of 16S rRNA gene recovered the new species as a member of the Agalychnis callidryas group. The presence of a red hue in the iris and a golden reticulated palpebral membrane, putative synapomorphies of the clade, support this hypothesis. Our anal-ysis suggests that Agalychnis terranova sp. nov is closely related to A. callidryas from Central America and is proposed as its sister species with an uncorrected genetic distance of 5.69% between these taxa. The phylogenetic position and the geographic distribution of the new taxon add new lights to the presence of a biogeographic disjunction between Middle America lowlands, the Pacific region and Magdalena River valley of Colombia.